Submucosal fibrosis in achalasia patients is a rare cause of aborted peroral endoscopic myotomy procedures - Wu, Qiu-Ning; Xu, Xiao-Yue; Zhang, Xiao-Cen; Xu, Mei-Dong; Zhang, Yi-Qun; Chen, Wei-Feng; Cai, Ming-Yan; Qin, Wen-Zheng; Hu, Jian-Wei; Yao, Li-Qing; Li, Quan-Lin; Zhou, Ping-Hong (Endoscopy, 2017)
Background and aims Peroral endoscopic myotomy (POEM) is now an established treatment for esophageal achalasia. The standard protocol ensures a smooth operation in most patients, but technical challenges and failures exist and little is known about the incidence, causes, and impact of aborted procedures. Here, using a large patient cohort, we attempted to answer these questions. Methods All patients admitted for planned POEM between August 2010 and July 2015 underwent chart review. Aborted POEM was defined as the inability to finish the procedure after submucosal injection. The cause of the failure, clinical course, management, and follow-up data were analyzed. Results Thirteen of the 1693 POEMs (0.77 %) were aborted. Out of the 13 failures, 12 (92.3 %) were due to severe submucosal fibrosis, which precluded tunneling, and one (7.7 %) was due to atrial fibrillation related to the electric current of the endoscopic knife. Submucosal fibrosis, prior Heller myotomy, and age ( ≥ 60 years) were related to technical failure, while a disease duration of ≥ 6 years, sigmoid esophagus, mucosal edema, and prior interventions were risk factors for the presence of fibrotic changes. In turn, fibrosis was correlated with a prolonged operation, longer hospital stay, more mucosal injuries, and more major perioperative adverse events. Finally, the yearly frequency of aborted POEMs decreased after the second year as operators became more experienced. Conclusions Aborted POEM is a rare event and is largely due to the presence of submucosal fibrosis, which not only causes increased procedural difficulties, but also gives rise to major adverse events.